(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the nutritional status and describe some factors related to nutrition in children with respiratory tract infections who were hospitalized at Thuy Nguyen General Hospital in 2024 - 2025. Research method: Cross-sectional descriptive study. Results: Among the 240 children participating in the study, the age group 1-<2 years old accounted for the highest proportion (29.6%), followed by the group 2-<3 years old (25.0%). The proportion of boys was (54.4%). The study results showed that the majority of hospitalized children with respiratory tract infections were moderate (87.0%), severe 11.7% and mild only 1.3%. The nutritional status of children showed a rate of underweight 14.6%, stunting 23.8% , wasting 12.1% and overweight and obesity 36.2%. The study identified several factors associated with stunting among children with acute respiratory infections, including gestational age less than 38 weeks (OR = 3.68; 95% CI: 1.45 to 9.37), residence in mountainous communes (OR = 5.83; 95% CI: 2.25 to 10.12), and early initiation of complementary feeding before 6 months of age (OR = 2.2; 95% CI: 1.2 to 3.6), with p < 0.05. Conclusion: Children with respiratory infections still have a fairly high rate of malnutrition and overweight/Obesity, and special attention is needed to care for these children both clinically and nutritionally.